A decision-tree-based system for student academic advising and planning in information systems programmes. (2nd December 2009) - Werghi, Naoufel; Kamoun, Faouzi Kam
This paper presents a Decision Support System (DSS) for student advising. The system aims to provide students with an automated programme planning and scheduling service that best fits their profiles while meeting academic requirements. After the literature survey and description of the system's architecture, the paper describes the new paradigm that models student advising as a search problem, whereby the search space is represented by a decision tree that embeds virtually all the instances of a student academic plan. Our approach has several advantages over previous rule-based advising systems. The system implicitly implements, via the decision tree, many academic rules; it allows a systematic and exhaustive browse of the different student plan instances; and it permits a methodological assessment and measurement of the appropriateness of a given student academic plan. An advanced prototype of the proposed advising system was successfully implemented.